Effectiveness of E-Modules Assisted by Heyzine Flipbooks Topics of Temperature and Heat Integrated in Ethnoscience to Improve Students' Literacy Science Abilities - Saputra, Lalu Muhammad Rispan Sugi; Doyan, Aris; Sukarso, AA (Journal of Science and Science Education, 2025)
This study explores the effectiveness of an e-module supported by Heyzine Flipbooks, specifically targeting the topics of temperature and heat integrated with ethnoscience, to enhance students' science literacy abilities. Conducted with 24 seventh-grade students in East Lombok, the research employed a Research and Development (R&D) approach, adhering to the 4D model (Define, Design, Develop, Disseminate). The results demonstrated a significant improvement in students' literacy, with average pre-test scores increasing from 29 to 77 post-test, resulting in an N-gain of 68%. The findings suggest that the e-module effectively enhances students' capabilities in explaining scientific phenomena, evaluating investigations, and interpreting data, particularly through the integration of local cultural contexts. The study concludes that digital learning media, when combined with ethnoscience, can foster meaningful science learning experiences